The effect of emotional intelligence on nurses’ job performance: the mediating role of moral intelligence and occupational stress - Rozita Cheraghi; Naser Parizad; Vahid Alinejad; Mehri Piran; Laleh Almasi (BMC Nursing)
Abstract Background Although previous studies have linked emotional intelligence to nurses’ job performance, research lacks how moral intelligence and occupational stress mediate this relationship. Addressing this gap is essential for improving nursing care outcomes. This study aims to determine the mediating effect of moral intelligence and occupational stress in this relationship among Iranian nurses. Methods This descriptive cross-sectional correlational study was conducted in Urmia Teaching Hospital from February to April 2022. Six hundred and twenty-one nurses were recruited using quota sampling. Data were collected using a demographic questionnaire, Lenik and Kiel’s Moral Intelligence Questionnaire (LK-MIQ), Siberia Schering’s Emotional Intelligence Questionnaire (SS-EISQ), Patterson’s Job Performance Questionnaire (P-JPQ), and the Nursing Stress Scale (NSS). Data were analyzed using IBM SPSS ver. 23 and Smart-PLS ver. 3.0. Results The effect of emotional intelligence on job performance was positive, direct, and weak (β = 0.099, t-value = 2.285, p = 0.023). Emotional intelligence had a negative, direct, and weak effect on moral intelligence (β = − 0.257, t-value = 4.754, p = 0.000) and a negative, direct, and moderate effect on occupational stress (β = − 0.316, t-value = 6.482, p = 0.000). Moral intelligence mediates the relationship between emotional intelligence and occupational stress (β = 0.0842, 95% CI: 0.0532, 0.1194). However, the mediating role of occupational stress between emotional intelligence and job performance was not supported (β = 0.003, 95% CI: − 0.0139, 0.0184). Conclusion Moral and emotional intelligence should be key criteria for selecting nursing staff and managers to create a safe, low-stress environment that boosts nurses’ job performance. Healthcare managers should promote nurses’ emotional intelligence by offering practical courses for enhancing nurses’ self-awareness, self-management, social awareness, and relationship management skills. It is essential to support moral intelligence by organizing educational classes that improve their integrity, responsibility, compassion, and forgiveness.